2016
DOI: 10.1155/2016/6479649
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of theπ-Bridge Influence with Different Units of Thiophene and Thiazole in Coumarin Dye-Sensitized Solar Cells

Abstract: Eight coumarin derivative dyes were studied by varying theπ-bridge size with different thiophene and thiazole units for their potential use in dye-sensitized solar cells (DSSC). Geometry optimization, the energy levels and electron density of the Highest Occupied Molecular Orbital and the Lowest Unoccupied Molecular Orbital, and ultraviolet-visible absorption spectra were calculated by Density Functional Theory (DFT) and Time-Dependent-DFT. All molecular properties were analyzed to decide which dye was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Decreased molar absorptivity as the result of substituting thiophene with thiazole has been previously noted by other authors,, and computational studies have shown that the transition oscillator strength continues to decrease with each additional substitution by thiazole . This difference in absorptivity can also be seen in the parent heterocycles themselves.…”
Section: Resultssupporting
confidence: 66%
“…Decreased molar absorptivity as the result of substituting thiophene with thiazole has been previously noted by other authors,, and computational studies have shown that the transition oscillator strength continues to decrease with each additional substitution by thiazole . This difference in absorptivity can also be seen in the parent heterocycles themselves.…”
Section: Resultssupporting
confidence: 66%
“…Hara et al studied coumarin based dyes with 1, 2 or 3 thiophene moiety, and found that the dye with two thiophene moieties to be effective dye in terms of electron injection into the conduction band of TiO 2 . Soto‐Rojo et al studied the chemical hardness ( ς ) of the coumarin based dyes containing different size of thiophene (one to three) linker and found that ς to decrease with increase in number of thiophene units. Considering ς as the measure of the resistance to the intramolecular charge transfer (ICT), a lower ς is desired for dye molecules to do ICT effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing only thiophene ( 1 ) have attracted widespread interest because of their linear and nonlinear optical properties with potential applications in telecommunications, optical computing, optical signal processing and for applications as sensitizers for DSSC . Due to their high structural stability, controllable electrochemical behavior, good performance in hole transporting ability, most efficient organic sensitizers that have A ‐bridge‐ D structure contain a π conjugation bridge composed of thiophene units among others.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the type of bridges, nowadays it is common to study π‐conjugated systems as thiophene and its derivatives. The use of thiazole‐based groups has also achieved interesting conversion efficiencies in DSSCs, mainly due to the red shift of the maximum absorption wavelength and the improvement of intramolecular charge transfer. Soto et al and Hara et al studied the performance of dyes with up to three thiophene units as the π‐bridge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation